Aesthetics and cognition in Kant's critical philosophy - Kukla, Rebecca, 1969- (Cambridge University Press, 2006)
This volume explores the relationship between Kant's aesthetic theory and his critical epistemology as articulated in the "Critique of Pure Reason" and the "Critique of the Power of Judgment". The essays, written specially for this volume, revise our understanding of core elements of Kant's epistemology, such as his notions of discursive understanding, experience, and objective judgment. They also demonstrate a rich grasp of Kant's critical epistemology that enables a deeper understanding of his aesthetics. Collectively, the essays reveal that Kant's critical project, and the dialectics of aesthetics and cognition within it, is still relevant to contemporary debates in epistemology, philosophy of mind, and the nature of experience and objectivity. The book also yields important lessons about the ineliminable, yet problematic place of imagination, sensibility and aesthetic experience in perception and cognition.